Computational Intelligence and Bioengineering - Masulli, Francesco (IOS Press, 2013)
This book is divided in the three main areas where Professor Antonina Starita was most active in the last period of her research activity: clustering and learning applications, biomedical applications, and motor control and evaluation. The part on clustering and learning applications opens with a contribution concerning the clustering of short-text corpora by Particle Swarm Optimization (PSO). The second contribution in this part investigates the use of Neural Networks (NN), and specifically of Recurrent NN, to interpret brain images obtained by functional Magnetic Resonance Imaging (fMRI). The first part of the book is closed by a contribution on the System for Paleographic Inspections (SPI) software suite.